CKD: A Guide to Higher Fiber Foods - Wendy J. Dahl; Nancy J. Gal (EDIS)
Living with chronic kidney disease (CKD) presents many challenges, and diet is one of them. People with CKD may find it difficult to consume enough fiber-rich foods while following the other diet recommendations for CKD. This 5-page guide will discuss the health benefits of fiber and provide some examples of fiber-rich foods that may be good choices for people with CKD. Written by Wendy J. Dahl and Nancy J. Gal and published by the UF/IFAS Department of Food Science and Human Nutrition, January 2018. http://edis.ifas.ufl.edu/fs305